2008
DOI: 10.1056/nejmoa0805002
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Extended-Release Dipyridamole versus Clopidogrel for Recurrent Stroke

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk original articleT h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
518
1
28

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 868 publications
(572 citation statements)
references
References 30 publications
(23 reference statements)
9
518
1
28
Order By: Relevance
“…However, whether HUK, a commercially available kallikrein–kinin system regulating medicine, is efficient in preventing recurrent stroke has not been reported yet. Previous studies have demonstrated that antiplatelet agents, statins, warfarin, and diabetic agents could reduce risk of recurrent stroke for specific stroke patient (Adams et al., 2008; Prasad, Kaplan, & Passman, 2012; Rother & Crijns, 2010; Sacco et al., 2008). In this study, we firstly found that implementation of HUK during initial hospitalization after acute onset was effective for preventing recurrent stroke within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether HUK, a commercially available kallikrein–kinin system regulating medicine, is efficient in preventing recurrent stroke has not been reported yet. Previous studies have demonstrated that antiplatelet agents, statins, warfarin, and diabetic agents could reduce risk of recurrent stroke for specific stroke patient (Adams et al., 2008; Prasad, Kaplan, & Passman, 2012; Rother & Crijns, 2010; Sacco et al., 2008). In this study, we firstly found that implementation of HUK during initial hospitalization after acute onset was effective for preventing recurrent stroke within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a side effect of the drug dipyridamole. However, there is no reason to believe that dipyridamole is a cause of poorer prognosis and increased occurrence of complications since no such correlation has been found in previous studies (Sacco et al., 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The Prevention Regimen for Effectively Avoiding Second Strokes (PRoFESS) study is a randomized, doubleblind, noninferiority trial with a 2×2 factorial design comparing aspirin-ERDP (25/200 mg) twice daily with clopidogrel (75 mg) daily for prevention of recurrent stroke [35]. A total of 20,332 patients were followed-up for a mean of 2.5 years.…”
Section: Aspirin Plus Dypyridimole Vs Clopidogrelmentioning
confidence: 99%
“…In the subgroup analysis of the PRoFESS study, there was a trend of benefit of clopidogrel in comparison to aspirin-ERDP, with an event rate of stroke of 9.4% as compared with 10.5% in patients who were recruited after a large artery stroke [35]. The comparison in lacunar stroke indicated that the 2 drugs were similar (i.e., clopidogrel [8.2%] vs combined therapy [7.9%]).…”
Section: Large Vessel Atherosclerosismentioning
confidence: 99%